PERAN VARIABEL MOTIVASI SEBAGAI PEMEDIASI PENGARUH KOMPENSASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN (STUDI KINERJA PEGAWAI PUSAT OLEH-OLEH KHAS BALI DI KABUPATEN GIANYAR) - Suwita Yanti, Ayu; Darsana, I Made (Berajah Journal, 2024)
The existence of a souvenir center in Gianyar Regency has an important role in supporting the sustainability of tourism in Bali. Strategic steps that can be taken to improve the quality of company services are by improving the performance of human resources. The aim of the research is to analyze the influence of work stress, compensation and motivation on the performance of employees at the Balinese souvenir center in Gianyar Regency, as well as analyzing the role of motivation in indirectly mediating the influence of compensation and work stress on employee performance. The research was conducted using a quantitative approach. The object of this research is the Balinese souvenir center which is located in the area of ​​Jl. Raya Batubulan, Sukawati District, Gianyar Regency. The population in the research was all employees who worked in the consumer service department (saleswomen and cashiers) totaling 96 people who made up the overall research sample (saturated sample). According to Sugiyono (2016) saturated sampling is a sampling technique when all members of the population are used as samples. The data collection method was carried out by means of a field survey using an instrument in the form of a closed questionnaire. The research data was then processed using descriptive statistical analysis PLS (Partial Least Square) analysis. Research findings showed that compensation and work stress had an effect on motivation, as well as compensation and motivation had an effect on employee performance, but work stress had no effect on employee performance. Meanwhile, to test the indirect effect of compensation on employee performance through motivation and work stress on employee performance through motivation, significant results were obtained.